The Jordanian passage to sustainable electrical power: case study of challenges and opportunities - Awada, Emad (Institute of Advanced Engineering and Science, 2025)
As the global energy sector faces significant challenges due to limited conventional resources and environmental concerns, many countries have adopted precautionary measures to secure and develop new energy resources. For instance, Jordan faces a severe shortage of natural conventional energy resources, compounded by rapid population growth driven by both locals and refugees. With over 90% of its energy imported, Jordan heavily depends on neighboring and international suppliers, leaving the country vulnerable and insecure due to political and economic fluctuations. To overcome these challenges, Jordan must establish comprehensive policies and plans to achieve energy production, conservation, and sustainability. This case study explores Jordan’s energy sources and security, highlighting strategies for long-term sustainable electrical energy development. The analysis focuses on addressing challenges, proposing alternative solutions, and advancing efficient plans for energy expansion. Key strategies include embracing renewable energy sources, enhancing conservation, and leveraging technological advancements to improve efficiency and a resilient energy sector.